Cholesterol's location in lipid bilayers. (September 2016) - Marquardt, Drew; Kučerka, Norbert; Wassall, Stephen R.; Harroun, Thad A.; Katsaras, John
Abstract : Graphical abstract: Abstract: It is well known that cholesterol modifies the physical properties of lipid bilayers. For example, the much studied liquid-ordered L o phase contains rapidly diffusing lipids with their acyl chains in the all trans configuration, similar to gel phase bilayers. Moreover, the L o phase is commonly associated with cholesterol-enriched lipid rafts, which are thought to serve as platforms for signaling proteins in the plasma membrane. Cholesterol's location in lipid bilayers has been studied extensively, and it has been shown – at least in some bilayers – to align differently from its canonical upright orientation, where its hydroxyl group is in the vicinity of the lipid–water interface. In this article we review recent works describing cholesterol's location in different model membrane systems with emphasis on results obtained from scattering, spectroscopic and molecular dynamics studies.